1999
DOI: 10.3109/10929089909148185
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Stereotaxy and Anterior Cervical Surgery

Abstract: Frameless stereotaxy can now be applied to procedures involving the anterior cervical spine. Potential benefits include accurate definition of the anatomy, demonstration of resection margins, and intraoperative guidance. The technique may prove particularly useful in cases of complex or disrupted anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Successful resection of a chordoma of the cranial base and upper spine was also achieved using frameless navigation in a patient with dislocation of the dens and medullary compression [12]. In addition, cadaveric studies have suggested that the accuracy of spinal instrumentation placement may be improved by the use of frameless stereotaxy [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful resection of a chordoma of the cranial base and upper spine was also achieved using frameless navigation in a patient with dislocation of the dens and medullary compression [12]. In addition, cadaveric studies have suggested that the accuracy of spinal instrumentation placement may be improved by the use of frameless stereotaxy [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Applying this technology in anterior spine surgery is more problematic because the anatomical landmarks necessary for device registration are relatively sparse. Nevertheless, its use has been described in cadaveric studies [1,6,8] and in a few clinical cases involving osteophyte resection, screw insertion for anterior cervical plate fixation [4], and transoral approaches to spinal pathology [11,12]. The transmandibular, circumglossal, retropharyngeal (TCR) approach provides excellent exposure of the skull base and upper cervical spine, and may similarly benefit from advantages of intraoperative navigation technologies, especially in patients with complex anatomy.…”
Section: Introductionmentioning
confidence: 99%